Comparison of X-ray fluorescent analysis and cupellation method for gold determination - Jotanović, Aida; Memić, Mustafa; Suljagić, Šemsa; Huremović, Jasna (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2012)
To make jewellery of gold, gold is alloyed with other metals. It is of great importance to accurately determine the total amount of pure gold in alloys used for making the jewellery and in jewellery made of gold, because it determines its value on the market. Several analytical methods are used for this purpose. This study was based on comparison of results of analysis of gold alloy for 14-carat jewellery obtained by non-destructive fluorescent analysis method and destructive cupellation method. The null hypothesis with 95% confidence level on equivalence in measurement precision of percent by percent mass of gold in three very similar gold alloy samples in reproducibility condition (three measurement series) for standard cupellation method and the method compared (validated), XRF method, has been confirmed. F-test did not confirm null hypothesis on precision equivalence for two mentioned analysis methods. There is a significant difference in variance values. However, the t-test was carried out, which verified the null hypothesis on equivalence between mean values of results achieved in two compared values. In order to confirm applicability of two methods, Z score was calculated giving values of less than 2, using statistical data from inter-laboratory program with 62 participating laboratories applying cupellation method, and 60 laboratories applying XRF method for analysis of gold alloy used in production of 14-carat jewellery.